Rheb Promotes Triglyceride Secretion and Ameliorates Diet-Induced Steatosis in the Liver - Du, Chongyangzi; Yang, Wanchun; Yu, Zongyan; Yuan, Qiuyun; Pang, Dejiang; Tang, Ping; Jiang, Wanxiang; Chen, Mina; Xiao, Bo (Frontiers in Cell and Developmental Biology, 2022)
Hepatosteatosis, characterized by excessive accumulation of lipids in liver, is a major health issue in modern society. Understanding how altered hepatic lipid metabolism/homeostasis causes hepatosteatosis helps to develop therapeutic interventions. Previous studies identify mitochondrial dysfunction as a contributor to hepatosteatosis. But the molecular mechanisms of mitochondrial dysfunction leading to altered lipid metabolism remain incompletely understood. Our previous work shows that Rheb, a Ras-like small GTPase, not only activates mTORC1, but also promotes mitochondrial ATP production through pyruvate dehydrogenase (PDH). In this study, we further demonstrate that Rheb controls hepatic triglyceride secretion and reduces diet-induced lipid accumulation in mouse liver. Genetic deletion of Rheb causes rapid and spontaneous steatosis in liver, which is unexpected from the role of mTORC1 that enhances lipid synthesis, whereas Rheb transgene remarkably reduces diet-induced hepatosteatosis. Results suggest that the hepatosteatosis in Rheb KO is an outcome of impaired lipid secretion, which is linked to mitochondrial ATP production of hepatocytes. Our findings highlight an under-appreciated role of Rheb in the regulation of hepatic lipid secretion through mitochondrial energy production, with therapeutic implication.